Wegener's granulomatosis: an analysis of 50 patients - M.G. Sabbadini; L. Praderio; M. Tresoldi; G. Ciboddo; S. Bianchi; S. Bozzolo; E. Bozzolo; G. Bonavida; G. Di Comite (PAGEPress Publications, 2011)
Objectives: Two evaluate the rate of different organs involvement in 50 patients with Wegener's Granulomatosis (GW), and to describe their clinical manifestations and their response to treatment. Methods: We evaluated 50 consecutive patients with GW, come to our attention from January 1987 to May 2003. 43 patients met the 1990 American College of Rheumatology (ACR) criteria for classification of GW; 7 patients the 1993 ELK criteria. Results: 82% of patients presented Ear/Nose/Throat (ENT) involvement, which is the most common site of inflammation. 22% of our patients had ENT-restricted disease; in 78% of cases disease extended to other organs. Lungs were involved in 72% of cases; kidney in 36%; eye in 24%; nervous system (NS) in 14% (central NS in 10% and peripheral NS in 4%); skin in 10%; heart in 8%; testis in 4%. Arthritis was present in 10% of patients. We discuss treatment of all patients and response to therapy of those 28 whose follow-up is available. Conclusions: Involvement of airways and kidney is by far the most common in GW, though potentially any other organ or system may be affected. The total rate of other organs involvement is 70%.